Organic fertilization improves soil aggregation through increases in abundance of eubacteria and products of arbuscular mycorrhizal fungi - Veronika Řezáčová (Nature Portfolio, 2021)
Abstract An important goal of sustainable agriculture is to maintain soil quality. Soil aggregation, which can serve as a measure of soil quality, plays an important role in maintaining soil structure, fertility, and stability. The process of soil aggregation can be affected through impacts on biotic and abiotic factors. Here, we tested whether soil management involving application of organic and mineral fertilizers could significantly improve soil aggregation and if variation among differently fertilized soils could be specifically attributed to a particular biotic and/or abiotic soil parameter. In a field experiment within Central Europe, we assessed stability of 1–2 mm soil aggregates together with other parameters of soil samples from differently fertilized soils. Application of compost and digestates increased stability of soil aggregates. Most of the variation in soil aggregation caused by different fertilizers was associated with soil organic carbon lability, occurrence of aromatic functional groups, and variations in abundance of eubacteria, total glomalins, concentrations of total S, N, C, and hot water extractable C. In summary, we have shown that application of compost and digestates improves stability of soil aggregates and that this is accompanied by increased soil fertility, decomposition resistance, and abundance of total glomalins and eubacteria. These probably play significant roles in increasing stability of soil aggregates.